Yoga Asana For Early Children's Physical Motoric Development - Harliana; Hermanto (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Physical and motor skills can affect the way people view themselves and their environment. Physical and motor development in early childhood is very influential in shaping the child's personality and development thoroughly. This research aims to describe asana yoga for the physical development of early childhood motor, using qualitative research case study of research site in PAUD Bali Public School Denpasar. The main data source consists of teachers, students and five-and six-year-old schoolgirls and a yoga instructor. Data collection procedures using observation techniques, interviews and documentation studies. While the data analysis is done during the ongoing research (on going proccess) with the stages of data reduction, data presentation and data verification as well as data validationin the form of data triangulation and member check. The results of the research was obtained by the data that the yoga asana for early childhood in PAUD Bali Public School Denpasar is a routine event Monday through Friday. Asana Yoga is performed for five to ten minutes with various types of poses including cobra pose, tree pose, lion pose, lotus pose. Asana Yoga is presented in the form of story telling and games adapted to the theme of the PAUD Daily Learning Implementation Plan (RPPH) such as animal themes, plants or environmental themes. The results of research in the field obtained data that, after the child performs regular yoga for three to six months with the correct movements, a significant increase in physical development as well motor and crude. Motor physical development in early childhood affects the development of the child in the future, to achieve optimal motor physical development should be given stimulation or stimulus in a variety of fun ways and in accordance with the growth stage of early childhood children